Keragaman Morfologi Lima Aksesi Terung Lokal (Solanum melogena L) - Vena Wahyu Mahardika; Annisa Khoiriyah; Elea Nur Aziza (JURNAL VIGOR, 2026)
This study evaluated the morphological and agronomic diversity of five local eggplant (Solanum melongena L.) accessions originating from Palembang (TR1), Kalimantan (TR2), Purbalingga (TR3), Riau (TR4), and Malang (TR5). The experiment was conducted at the Celeban Teaching Factory, Polbangtan Yogyakarta–Magelang, using a randomized complete block design with five replications. The morphological traits evaluated are plant growth habit, stem anthocyanin intensity, stem pubescence, leaf shape and lobing, flower color, fruit shape, fruit apex shape, calyx spines, fruit surface glossiness, fruit skin and flesh color, and fruit markings. The agronomic traits measured included plant height, stem diameter, leaf length and width, fruit length and diameter, number of fruits per plant, individual fruit weight, days to flowering, and days to harvest. The results showed considerable variation among the five accessions for most morphological and agronomic traits. TR1 exhibited the greatest plant height, whereas TR2 had the largest leaves, thickest stems, widest fruits, and highest individual fruit weight. TR3 produced the highest number of fruits per plant, while TR4 had the greatest fruit lengthTR5 showed the lowest plant height and fruit number. The identified variation provides valuable information for germplasm conservation and collection with desirable agronomic and market-oriented characteristics.